Synthesis and evaluation of the cholic acid derivatives with multitrifluoroacetylbenzoyl (TFAB) groups as carbonate ionophores - Pyun, HJ; Chu, JH; Yoon, W; Jun, YM; Kim, DJ (KOREAN CHEMICAL SOC, 1999)
Several cholic acid derivatives containing 1-3 trifluoroacetylbenzoyl (TFAB) moieties were synthesized using selective acetylations, hydrolysis and/or oxidation of cholic acid derivatives and tested as receptors for a carbonate ion through solvent extraction method. The compounds having two and three TFAB moieties exhibited enhanced binding affinities toward a carbonate ion in comparison with those with one TFAB group and the extent of complex formation also depended on the position of TFAB group attached.
Keywords: SELECTIVE MEMBRANE-ELECTRODE; MACROCYCLE INTERACTION; KINETIC DATA; TRIFLUOROACETOPHENONE DERIVATIVES; ASYMMETRIC-SYNTHESIS; MOLECULAR TWEEZERS; ION; DIOXIDE; CATIONS; DESIGN